Ractopamine for Pigs: A Review about Nutritional Requirements - Aloízio Soares Ferreira; Gregório Murilo de Oliveira Júnior; Francisco Carlos de Oliveira Silva; Rita Flávia Miranda de Oliveira; Edney Pereira da Silva (Journal of Basic & Applied Sciences, 2013)
Heavy weight pigs tend to deposit greater quantities of fat than protein. To work around this situation, ractopamine has been used in the finishing stage. In environments with moderate temperatures, ractopamine in pig diets in the finishing phase may increase rates of weight gain and improve feed efficiency without affecting feed intake. Ractopamine increases needs of pigs in terms of lysine, phosphorus and energy. The effects of ractopamine in pigs raised under conditions of heat stress have been observed in weight gain, feed efficiency and muscle deposition rate, but not on reducing the amount of fat in pigs weighing between 95.0 and 120.0 kg. Ractopamine has promoted the increase in quantity of meat on the carcass, without altering flavor and tenderness. The weight of some organs is affected by the use of ractopamine, especially in animals under conditions of heat stress. There is need for more research relating to the effects of ractopamine with the welfare of pigs with at least 95.0 kg.